miRNAs and death receptors - Park, Sun-Mi (2008)
Death receptors induce apoptosis through either the Type I or Type II pathway. In Type I cells, the initiator caspase-8 directly activates effector caspases such as caspase-3, whereas in Type II cells, the death signal is amplified through mitochondria thereby activating effector caspases causing cell death. Recently, there have been advances in elucidating the early events in the CD95 signaling pathways and how posttranslational modifications regulate CD95 signaling. This review will focus on recent insights into the mechanisms of the two different types of CD95 signaling pathways, and will introduce miRNAs as regulators of death receptor signaling.